Outcomes of curative (chemo)radiotherapy for patients with non‐p16 positive head and neck squamous cell carcinoma who are borderline for curative treatment. Issue 2 (9th February 2020) - Xing, Daniel; Tiong, Albert; Bressel, Mathias; Rischin, Danny; Tran, Phillip; Corry, June
Abstract: Introduction: Appropriate selection of head and neck squamous cell cancer (HNSCC) patients for curative treatment is difficult, and it is a very understudied issue. The aim of this study was to review the outcomes of curative intent treatment in non‐p16 positive HNSCC patients assessed as having borderline curability. Methods: A single institution retrospective review of the clinical outcomes of non‐p16 positive HNSCC patients with borderline curability. Predefined criteria for borderline curability were as follows: (i) T4 and/or N3 disease; or (ii) ECOG status ≥2; or (iii) age ≥75 years. Results: A total of 114 patients were identified. A total of 56 had N3/T4, 32 were >ECOG 2 and 57 were >75 years. A total of 29 had two or more borderline curability criteria. Progression‐free survival rate (PFS) at 1 and 2 years was 72% (95% confidence interval (CI), 63–79) and 53% (95% CI, 43–62), respectively. Overall survival (OS) at 1 and 2 years was 76% (95% CI, 67–83) and 61% (95% CI, 51–69), respectively. On multivariable analysis, the only independent prognostic factor for OS was the adult comorbidity evaluation‐27 (ACE‐27) grade (HR 1.4; 95% CI, 1.1–1.8; P  = 0.018). Conclusions: Patients with borderline curability criteria treated with curative intent achieved good PFS and OS. ACE‐27 was an important prognostic factor in this population.